Lacustrine sedimentation patterns at the Northern Antarctic Peninsula and surroundings as a response to late Holocene and Modern Climate changes - Heitor Evangelista; Sergei Verkulich; Bulat Mavlyudov; Mariza P. Souza Echer; Marcus Vinicius Licinio; Gerd Dercon; Felipe García-Rodríguez; Arthur A. Neto; Stephanie Kusch; Rodrigo C. Abuchacra; Anna B.J. Oaquim; Sérgio J. Gonçalves; et al. (Scientific Reports)
Abstract The Northern Antarctic Peninsula (NAP) and the West Antarctic Ice Sheet (WAIS) are likely to respond rapidly to climate changes by increasing the collapse of peripheral ice shelves and the number of days above 0 °C. These facts make this region a representative hotspot of the global sea level rise and the location of one of the global climate tipping points (thresholds in the Earth system whose changes may become irreversible, if exceeded). Understanding the climate evolution of the NAP, based on past evidences, may help infer its future scenario. Herein, from a comprehensive survey of lacustrine sedimentation in proglacial and periglacial lakes/ponds, we investigated the impact of climate changes on the terrestrial environment in two complementary time scales (Late Holocene and contemporary age). For the longer time scale, regional climate database and biogeochemical properties of Lake Long/NAP sediment core, suggest warming between 4.0 and 2.0 kyr BP following a cooling phase towards the present, that endorse previously suggested Late Holocene Neoglacial (LHN). We attribute the LHN phase to a combined action of long-term decline in total solar irradiance, the Andean volcanism and the El Niño Southern Oscillation. For the contemporary age, we found a rapid coupled response of atmosphere/cryosphere/lithosphere to present warming levels.